2019
DOI: 10.1002/ab.21862
|View full text |Cite
|
Sign up to set email alerts
|

The longitudinal relationships of interpersonal openness trait, hostility, and hostile attribution bias

Abstract: While the relationship between personality, hostility, and hostile attribution bias (HAB) has been explored in previous studies, their longitudinal relationship is unclear, and no related study has utilized the indigenous Chinese personality. This research explored the longitudinal relationships of interpersonal openness (IO; an indigenous Chinese personality construct), hostility, and HAB. The 942 valid participants (38.5% male, mean age = 20.83, standard deviation =  1.04) were from six different provinces i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In particular, hostility bias may be stronger among aggressive and emotionally disturbed youth, for example, those with conduct disorder (Crick & Dodge, 1994), among children, adolescents, adults high in aggression (Epps & Kendall, 1995; Tuente, Bogaerts, & Veling, 2019), and among inmates (Bateman & Fonagy, 2008a; Schönenberg & Jusyte, 2014). People high in HAB tend to respond aggressively to perceived provocation, thus HAB is a key risk factor for antisocial behaviours (Wang & Xia, 2019; Yeager, Miu, Powers, & Dweck, 2013).…”
mentioning
confidence: 99%
“…In particular, hostility bias may be stronger among aggressive and emotionally disturbed youth, for example, those with conduct disorder (Crick & Dodge, 1994), among children, adolescents, adults high in aggression (Epps & Kendall, 1995; Tuente, Bogaerts, & Veling, 2019), and among inmates (Bateman & Fonagy, 2008a; Schönenberg & Jusyte, 2014). People high in HAB tend to respond aggressively to perceived provocation, thus HAB is a key risk factor for antisocial behaviours (Wang & Xia, 2019; Yeager, Miu, Powers, & Dweck, 2013).…”
mentioning
confidence: 99%
“…This result supports the psychosocial vulnerability model in terms of change trends. Individuals with high levels of hostile attribution bias have less social support, worse interpersonal relationships and fewer available psychological resources, and hostile attribution bias is a persistent and stable cognitive tendency (Wang & Xia, 2019). Su et al (2021) conducted a longitudinal study on hostile attribution bias and aggressive behaviour among Chinese college students and found that hostile attribution bias, as a stable cognitive factor, positively predicts aggressive behaviour in college students.…”
Section: Discussionmentioning
confidence: 99%
“…Hostility was assessed using the Brief Cook-Medley Hostility Scale (Strong et al, 2005). The Chinese version of this scale has demonstrated good reliability and validity (Wang & Xia, 2019;Wang et al, 2021).…”
Section: Hostilitymentioning
confidence: 99%